2007
DOI: 10.1158/1078-0432.ccr-07-0460
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Single-Agent Pertuzumab, a Human Epidermal Receptor Dimerization Inhibitor, in Patients with Non–Small Cell Lung Cancer

Abstract: Purpose: Pertuzumab, a first-in-class human epidermal receptor 2 (HER2) dimerization inhibitor, is a humanized monoclonal anti-HER2 antibody that binds HER2's dimerization domain and inhibits HER2 signaling. Based on supporting preclinical studies, we undertook a Phase II trial of pertuzumab in patients with recurrent non^small cell lung cancer (NSCLC). Experimental Design: Patients with previously treated NSCLC accessible for core biopsy and naive to HER pathway inhibitors were treated with pertuzumab i.v. on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…Pertuzumab is a humanized monoclonal antibody directed against HER2 that is designed to inhibit dimerization of HER2 with other HER family receptors including EGFR, HER3, and HER4 (5)(6)(7). Previous phase II studies in NSCLC have shown signs of pharmacodynamic activity in response to single-agent pertuzumab therapy in patients with advanced or recurrent NSCLC, though no partial or complete responses were observed (8,9). Pertuzumab and erlotinib inhibit overlapping but distinct aspects of HER family signaling, and other studies have suggested that development of acquired resistance to EGFR inhibitors is associated with upregulation and increased dependency on other HER family members such as HER3 (10), providing a strong rationale for studying the safety and efficacy of the combination of these agents in advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Pertuzumab is a humanized monoclonal antibody directed against HER2 that is designed to inhibit dimerization of HER2 with other HER family receptors including EGFR, HER3, and HER4 (5)(6)(7). Previous phase II studies in NSCLC have shown signs of pharmacodynamic activity in response to single-agent pertuzumab therapy in patients with advanced or recurrent NSCLC, though no partial or complete responses were observed (8,9). Pertuzumab and erlotinib inhibit overlapping but distinct aspects of HER family signaling, and other studies have suggested that development of acquired resistance to EGFR inhibitors is associated with upregulation and increased dependency on other HER family members such as HER3 (10), providing a strong rationale for studying the safety and efficacy of the combination of these agents in advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…For molecularly targeted therapies, several small studies in selected NSCLC patients have evaluated FDG-or FLT-PET changes (20)(21)(22)(23)(24)(25). However, for molecularly targeted therapies, it has not yet been established whether these imaging approaches provide a clinically meaningful assessment of therapeutic activity in NSCLC, particularly in the absence of tumor shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…A phase I clinical trial in which 43 NSCLC chemonaïve patients were treated with pertuzumab i.v. every 3 weeks found 9.3% grade ≥ 3 adverse events and no response [136]. Lastly, a phase II clinical trial assesses the response to F-18-fluorodeoxyglucose positron emission tomography of the combination of erlotinib and pertuzumab and results are pending [137].…”
Section: Anti-her2 Mabmentioning
confidence: 99%